The effect of perceived regional accents on individual economic behavior: A lab experiment on linguistic performance, cognitive ratings and economic decisions - Stephan Heblich; Alfred Lameli; Gerhard Riener (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
Does it matter if you speak with a regional accent? Speaking immediately reveals something of one's own social and cultural identity, be it consciously or unconsciously. Perceiving accents involves not only reconstructing such imprints but also augmenting them with particular attitudes and stereotypes. Even though we know much about attitudes and stereotypes that are transmitted by, e.g. skin color, names or physical attractiveness, we do not yet have satisfactory answers how accent perception affects human behavior. How do people act in economically relevant contexts when they are confronted with regional accents? This paper reports a laboratory experiment where we address this question. Participants in our experiment conduct cognitive tests where they can choose to either cooperate or compete with a randomly matched male opponent identified only via his rendering of a standardized text in either a regional accent or standard accent. We find a strong connection between the linguistic performance and the cognitive rating of the opponent. When matched with an opponent who speaks the accent of the participant's home region - the in-group opponent - individuals tend to cooperate significantly more often. By contrast, they are more likely to compete when matched with an accent speaker from outside their home region, the out-group opponent. Our findings demonstrate, firstly, that the perception of an out-group accent leads not only to social discrimination but also influences economic decisions. Secondly, they suggest that this economic behavior is not necessarily attributable to the perception of a regional accent per se, but rather to the social rating of linguistic distance and the in-group/out-group perception it evokes.
Keywords: 330